Comparative review of burns with inhalation injury in a tertiary hospital in a developing country (2016)
Objective. Inhalation injury is an acute respiratory tract insult caused by direct thermal injury, carbon monoxide poisoning, or toxic chemical inhalants, such as fumes, gases, and mist. The aim of this study is to review the authors’ experiences in a regional burn unit in a developing country. Methods. The university college Hospital, Ibadan, Nigeria prospective burn unit database was retrospectively reviewed from January 2001to December 2013and analyzed using SPSS software, version 16 (SPSS Inc, Chicago, IL). Results. There were 840 patients in all, 63% (527) had cutaneous burns only, while 37%(313) had associated inhalation injury. There was a male preponderance in both groups. Those with cutaneous burns only and those with associated inhalation injury had a male to female ratio of 1.6;1 and 1.5:1, respectively. The mean ages were ears (inhalation injury) and 21 years ± 17 years cutaneous burn only) (P < 0.05). The mean total body surface area (TBSA) of the burn injuries was 55% (inhalation injury) and 25% cutaneous burn only) (P < 0.05). Burn injury occurred most frequently between 19.00 hours and 24.00 hours, and 56% of burn es that occurred during this time were associated with inhalation injury (P < 0.05). Major causes of burns were flames and scalding (86.2%). Mortality was 71% in patients with inhalation and 26% in patients with cutaneous burns only (P < 0.05). Conclusion. The association of inhalation injury with cutaneous burns portends a grave condition. An upgrade of expertise and infrastructure in the management of these patients is necessary in order to improve outcomes.